Farmers' willingness to invest in mechanized maize shelling and potential financial benefits: evidence from Tanzania - Kotu, Bekele Hundie; Manda, J.; Mutungi, C.; Fischer, G.; Gaspar, A. (Wiley, 2023)
Sub-Saharan Africa has the least mechanized agriculture in the world due to various reasons including low effective demand at farm level, low policy attention, and ineffective mechanization strategies. However, the situation has changed since recently in favor of mechanization while limited empirical evidence is available on how mechanization can be enhanced among smallholder farmers. In this study, we explore farmers' willingness to invest in mechanization services by considering the group business model (GBM) and the individual business model (IBM) of mechanized maize shelling in Tanzania. Moreover, we analyze the potential financial benefit for those farmers who would like to invest in mechanized maize shelling. We use data mainly collected through a household survey and apply econometric and mathematical models for analysis. The results show that about 65% of the sample farmers are willing to invest in mechanized maize shelling within the GBM, while about 10% of them would like to do so within the IBM. Moreover, the results show that investment in mechanized maize shelling is profitable considering both small-scale (4 and 7 HP engine capacity) machines and medium-scale (16 and 20 HP engine capacity) machines. The results show that expanding agricultural mechanization in Tanzania through investments coming from smallholder farmers, as also experienced elsewhere, is possible while they suggest that policy instruments such as targeted loan programs, entrepreneurial and technical trainings, and smart subsidies or tax exemptions are important to encourage and enable smallholder farmers to participate in the mechanization supply chain. [EconLit Citations: Q120, Q130, D250].